Satellite Observations of the Seasonal Evolution of Total Precipitable Water Vapour over the Mediterranean Sea - J. L. Palau; F. Rovira; M. J. Sales (Advances in Meteorology)
This study shows satellite observations and new findings on the time and spatial distribution of the Total Precipitable Water (TPW) column over the Mediterranean Sea throughout the year. Annual evolution and seasonality of the TPW column are shown and compared to the estimated net evaporation over the Mediterranean Sea. Daily spatiotemporal means are in good agreement with previous short-term field campaigns and also corroborate hypothesis and conclusions reached from previous mesoscale modelling studies: (a) from a meteorological point of view, Mediterranean Basin should be considered as two different subbasins (the Western and the Eastern Mediterranean); (b) accumulation processes may affect the radiative balance at regional scale and the summer precipitation regimes. Furthermore, these satellite observations constitute strong empirical evidences that, (a) from late May to early October, contrary to what happens in the Eastern Mediterranean Basin (EMB), there is a net accumulation of TPW on the Western Mediterranean Basin (WMB) that favours the instability of the atmosphere, (b) there is a seasonal anticorrelation between the seasonal variability of the TPW column over the two Mediterranean subbasins, (c) solar radiation can not be the only driver for the annual variability of the TPW column over the Mediterranean Sea, and (d) both previous features are seasonally dependent and, therefore, their effects on the TPW column are attenuated by annual variability.